Introducing CILLCO: A corpus model of vernacular Indonesian as a cultural capital - Pradita, Intan; Puspitasari, Devi Ambarwati; Karlina, Yenny; Sukma, Bayu Permana (Jurnal Komunikasi, 2026)
Despite Indonesia's extraordinary linguistic diversity, the communicative realities of vernacular Indonesian remain significantly underrepresented in existing corpus resources, most of which privilege formal and written registers. This study introduces CILLCO (Corpus of Indonesian Language, Linguistics, and Communities), a multimodal digital corpus jointly developed by the Research Center for Language, Literature, and Community at the National Research and Innovation Agency (BRIN) and the English Department of Universitas Islam Indonesia (UII), with the objective of documenting and analyzing vernacular language varieties as they occur in everyday spoken, digital, and community contexts. CILLCO was constructed using a multi-component design grounded in the Lancaster corpus methodology. CILLCO integrates three primary data streams such as spoken vernacular, digital vernacular, and community narrative texts that were collected through field recording, web scraping, and community collaboration across five macro-regions of Indonesia. As of 2025, the corpus comprises approximately 2 million tokens annotated through a layered framework that includes tokenization, part-of-speech tagging, morphological analysis, sociolinguistic metadata, and pragmatic discourse marking. Results reveal that vernacular Indonesian is characterized by systematic morphosyntactic simplification, a rich inventory of pragmatic particles showing regional variation, orthographic play in digital communication, and extensive code-mixing with English and regional languages. These findings demonstrate that colloquial Indonesian constitutes a coherent, rule-governed linguistic system rather than a deviation from standard norms. The implications of this study extend across corpus linguistics, communication studies, and digital humanities, offering an empirical foundation for investigating language use, identity, and sociocultural change in Indonesia and, more broadly, for decentered, corpus-driven communication research in Southeast Asia.